2020
DOI: 10.1177/1756286420964673
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of patent foramen ovale in the Greek population is high and impacts on the interpretation of the risk of paradoxical embolism (RoPE) score

Abstract: Background: The risk of paradoxical embolism (RoPE) score calculates the probability that patent foramen ovale (PFO) is causally related to stroke (PFO attributable fraction, PFOAF), based on PFO prevalence in patients with cryptogenic stroke (CS) compared with that in the general population. The latter has been estimated at 25%; however, PFO prevalence in nonselected populations varies widely. Methods: Since PFO prevalence in Greece remains unknown, we evaluated it and we calculated PFOAF stratified by RoPE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The average Swiss, German, and Italian PFO closure rates (average 5 per 100,000 persons) appears to be substantially higher than in France (2.9 per 100,000) and the UK (0.5 per 100,000) [ 13 ]. While differing procedure rates across countries could be caused by health care system related differences [ 29 ] or differences in the prevalence of PFO [ 30 ] and the PFO detection rates, the high regional variation in PFO closure within Switzerland, a country with a homogenous health care system and good access to care, is unclear. With a low variation in stroke rates across Switzerland [ 33 ] and assuming similar patient preferences across Swiss regions, the variation is most likely partially due to differing local practice patterns [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average Swiss, German, and Italian PFO closure rates (average 5 per 100,000 persons) appears to be substantially higher than in France (2.9 per 100,000) and the UK (0.5 per 100,000) [ 13 ]. While differing procedure rates across countries could be caused by health care system related differences [ 29 ] or differences in the prevalence of PFO [ 30 ] and the PFO detection rates, the high regional variation in PFO closure within Switzerland, a country with a homogenous health care system and good access to care, is unclear. With a low variation in stroke rates across Switzerland [ 33 ] and assuming similar patient preferences across Swiss regions, the variation is most likely partially due to differing local practice patterns [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…system related differences [29] or differences in the prevalence of PFO [30] and the PFO detection rates, the high regional variation in PFO closure within Switzerland, a country with a homogenous health care system and good access to care, is unclear. With a low variation in stroke rates across Switzerland [33] and assuming similar patient preferences across Swiss regions, the variation is most likely partially due to differing local practice patterns [57].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Universally about a quarter of adults have PFO [ 2 , 3 ]. A study on Greek population showed a much higher prevalence (42.7% of healthy population, and 49% of patients with cryptogenic stroke) [ 4 ]. No data exist regarding the prevalence of PFO in the general population in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the incidence of a right-to-left shunt (RLS) is ~50–60% in migraineurs, which is similar to that of photophobia ( 7 , 8 ). RLS allows micro-emboli, air emboli, and partial unoxygenated venous blood to enter the systemic circulation directly, which can trigger cortical spreading depression (CSD) ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%